Peran Orang Tua dalam Mendidik Kerohanian AnakUsia Dini Berdasarkan Ulangan 6 - Sabda Budiman (Institut Agama Kristen Negeri Manado, 2022)
The main and early education centers also started from the family environment. One of the important aspects that needs to be educated is the spirituality of the child. Parents have a responsibility to work on this. This spiritual education needs to be done from an early age, given that this age is the age at which the child can easily record, imitate and digest what he sees and feels. The purpose of writing this scientific paper is to explain the role of parents in educating early childhood spirituality based on Deuteronomy 6. The author uses qualitative research methods. The role of parents in educating early childhood spirituality based on deuteronomy chapter 6 is by teaching the values of truth repeatedly, inviting children to worship God, and telling the history of the experience of faith with God to children. The main purpose is for the child to know and accept the Savior and live more and more like Christ. Pusat pendidikan utama dan mula-mula juga berawal dari lingkungan keluarga. Salah satu aspek penting yang perlu dididik ialah kerohanian anak. Orang tua memiliki tanggung jawab untuk mengerjakan ini. Pendidikan kerohanian ini perlu dilakukann sejak anak usia dini, mengingat bahwa usia ini adalah usia di mana anak mudah merekam, meniru dan mencerna apa yang ia lihat dan rasakan. Tujuan dari penulisan karya ilmiah ini ialah untuk memaparkan peran orang tua dalam mendidik kerohanian anak usia dini berdasarkan Ulangan 6. Penulis menggunakan metode penelitian kualitatif. Adapun peran orang tua dalam mendidik kerohanian anak usia dini berdasarkan kitab Ulangan pasal 6 yaitu dengan cara mengajarkan nilai-nilai kebenaran dengan berulang-ulang, mengajak anak untuk beribadah kepada Tuhan, dan menceritaan sejarah pengalaman iman bersama Tuhan kepada anak. Tujuan utamanya ialah supaya anak mengenal dan menerima Sang Juruselamat serta hidup terus bertumbuh semakin serupa dengan Kristus.